The Aesthetics of Quranic Intertextuality in the Contemporary Algerian Novel Rih Youssef’s Novel of Allaoua Koussa A Model - Kaddum, Mahmud (Fırat University, 2022)
turned to. Literary scholars have taken care of it in various literary arts and celebrated it as a kind of intersection of texts that gives the text richness and contributes to distancing it from the limits of directness and rhetoric. From this point of view, this study aims to reveal the extent to which Qur’anic intertextuality contributes to the granting of aesthetics to contemporary Algerian novelist discourse Rih Youssef, aesthetic and functional. The study relied on the descriptive analytical method to present the nature of intertextuality in general and the manifestations of Qur’anic intertextuality, especially in this narrative text, to conclude that the narration follows the approach of the story of Joseph, peace be upon him. The use of this linguistic technique is only a reflection of the saturation of the writer’s spirit with the story's meanings and its psychological, social, intellectual, and artistic values, which made him a lot of quoting and including from the Qur’anic text vocabulary, structures, and stories.

Bu çalışma, Kur'an metinlerarasılığının, cıva ile karakterize edilen çağdaş Cezayir romancı söylemine estetik kazandırmaya ne ölçüde katkıda bulunduğunu, Kur'an'ın haberci metin parçalarıyla olan ilişkisi ve etkileşimi ile karşılaştırmalı olarak ortaya koymayı amaçlamaktadır. Sahibi kasıtlı olarak estetik ve işlevsel sorunları gündeme getiren Allaoua Koussa'nın “Rih Youssef” romanında vücut bulan potasındaki enginliği ve fitili; Kur'an metinlerinin sözcük dağarcığından, yapılarından ve hikâyelerinden alıntı yapmak ve yerleştirmek gibi, bu sorgulamayı betimleyici-analitik yaklaşımı genel olarak metinlerarasılığın doğasını ve özel olarak Kur'an metinlerarasılığının tezahürlerini bu anlatıda sunmak için bir yolculuk olarak almak gibi. Bu, romanın ilerlemesinin, Yusuf'un -barış onun üzerine olsun - hikâyesinin yaklaşması ve bu dilsel tekniğin kullanılması üzerine olduğu sonucuna varmak, sadece yazarın ruhunun bu anlamlarla doygunluğunun bir yansımasıdır. Hikâye ve onun psikolojik, sosyal, entelektüel ve sanatsal değerleri.
Çağdaş Cezayir Romanında Kur'an Metinlerarasılığının Estetiği Rih Youssef'in Allaoua Koussa Romanı Bir Örnek
Keywords: Religious Studies; Din Araştırmaları